Radiosonde level2 measurements in NetCDF format gathered during MARIA S. MERIAN cruise MSM114/2 (ARC) - Laura Köhler; Lennéa Hayo; Daria Paul; Julia Windmiller (PANGAEA, 2024)
The ship campaign MSM114/2 (ARC) with the German research vessel Maria S. Merian took place from 22 January to 23 February, 2023. The campaign started in Mindelo, Cape Verde, and ended in Punta Arenas, Chile. During the campaign, the Intertropical Convergence Zone (ITCZ) was completely crossed three times at an almost constant longitude of 23W yielding three profiles of the ITCZ. Afterwards, a storm was passed in the Roaring Forties, in the South Atlantic. Here, we present level 2 radiosonde data as part of a series of standardised data sets of the atmospheric and oceanographic observations gathered during the ARC campaign. The radiosonde level 2 data are interpolated to altitude levels with distance 10 m. They include temperature, dew point temperature, potential temperature, mixing ratio, specific and relative humidity, wind speed and direction as well as the horizontal wind components u and v as function of start time and altitude.
In: Köhler, Laura; Baranowski, Dariusz B; Brennek, Michał; Ciuryło, Michał; Hayo, Lennéa; Jansen, Friedhelm; Kepski, Daniel; Kinne, Stefan; Latos, Beata; Lobo, Bertrand; Marke, Tobias; Nischik, Timo; Paul, Daria; Pietruczuk, Aleksander; Stammes, Piet; Szkop, Artur; Tuinder, Olaf; Windmiller, Julia (2024): Standardized data sets of the atmospheric and oceanographic observations gathered during MARIA S. MERIAN cruise MSM114/2 (ARC) [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.966616